1958
DOI: 10.1071/ar9580363
|View full text |Cite
|
Sign up to set email alerts
|

Fleece characters and their influence on wool production per unit area of skin in Merino sheep

Abstract: The variations in fleece characters and the dependence of wool production per unit area of skin on these characters were studied with 15 sheep in both a medium and a strong-wool strain of Merino. Small but significant differences in staple length and fibre diameter were found between regions on the body, whereas differences in density were large. The variation in density was about three times as large as those in staple length and fibre diameter. Distinct dorsoventral and anteroposterior gradients over the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Doney (1959) suggested that within a sheep, variation in the mean length and mean diameter is influenced by the local density of follicle population. Earlier, Young & Chapman (1958) defined the role of density in determining the level of production; in fine wool breeds density plays the major role in wool production whereas in strong wool breeds the length and diameter assume the major importance.…”
Section: Discussionmentioning
confidence: 99%
“…Doney (1959) suggested that within a sheep, variation in the mean length and mean diameter is influenced by the local density of follicle population. Earlier, Young & Chapman (1958) defined the role of density in determining the level of production; in fine wool breeds density plays the major role in wool production whereas in strong wool breeds the length and diameter assume the major importance.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that the anterior or first-formed follicle groups (Carter and Hardy 1947) and the relatively denser dorsal follicle groups (Young and Chapman 1958) were .most resistant to the effects of flumethasone .. .ltis a matter of speculation whether the treatment was reversing the original orderof follicle group development, and although the possibility exists that the greater density of fibres along the dorsum, relative to the somewhat sparser follicle populations ventrally and cervically, may reduce the quantity of hormone available to each fibre target, this explanation appears to be remote when the response of cervical follicles is taken into account. Another related question which needs' additional research is whether the unbroken fibres represented a random sample of the fibre population in any region.…”
Section: Discussionmentioning
confidence: 99%
“…Young and Chapman (1958) recorded variation in wool production and quality over 11 body sites in 2 strains of 3.5-to 4.5-year-old Merino ewes, and found that staple length was greatest in the midbody region, while fibre diameter increased and fibre density decreased from anterior to posterior regions. In the vertical plane, both staple length and fibre diameter tended to decrease away from the midbody region, while fibre density decreased from the dorsal to ventral sites.…”
Section: Introductionmentioning
confidence: 98%